PENGARUH PEMBELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMK NEGERI 1 SUMEDANG - Tria Sri Jayanti; Nanang Dalil Herman; Amar Mufhidin (Universitas Pendidikan Indonesia (UPI), 2023)
The unemployment rate in Indonesia has a large number, one of which is vocational high school (SMK) graduates. The number of unemployed is due to the minimal number of jobs where the number of job seekers is more than the number of jobs. SMK students are not only designed to be ready to work but also in terms of entrepreneurship, one of which is through Creative Product Learning and Entrepreneurship. Creative Product and Entrepreneurship Learning is designed to train students to have entrepreneurial character, training in making creative products and direct experience in entrepreneurship. The purpose of this study was to determine the effect of learning creative products and entrepreneurship on interest in entrepreneurship. The research method used in this study is a quantitative method. The subject of this research is the class XII students of DPIB SMK Negeri 1 Sumedang with a total sample of 84 people. Data collection techniques using a questionnaire instrument. The results showed that the Creative Product Learning and Entrepreneurship variable (X) was in the medium category and the Entrepreneurial Interest variable (Y) was in the medium category as well. Based on the results of the study, there is a positive and significant influence between learning creative products and entrepreneurship on the entrepreneurial interest of students at SMK Negeri 1 Sumedang. It is hoped that in the implementation of creative product learning and entrepreneurship, improvements and experiences regarding entrepreneurship are needed in accordance with the student's field of expertise so that learning can further increase student interest in entrepreneurship.